Giving voice: An analysis of the media’s reporting on the failed insurrection, looting and arson in July 2021 in South Africa. - Masiza, Simphiwe (University of the Witwatersrand, Johannesburg, 2024)
This dissertation explores what the dominant voices in the media coverage of the failed insurrection of July 2021 revealed about the ideologies at play? The research further probed what discourse and ideologies were revealed regarding the way the failed insurrection, looting, and arson that took place in July 2021 were covered. The dissertation provides a background discussion of the media landscape. It then discusses the relevant literature review focusing on issues of media voices, absence, representation, and underrepresentation of certain groups in the media. The research employed qualitative discourse analysis on forty (40) online articles. Furthermore, it tested the findings using a radical democratic, symbolic annihilation and a political economy of the media theoretical framework. The limitations of the research surfaced due to the reliance on daily publications such as the Daily Sun, Sowetan as well and the Independent Online articles (IOL) mainly because weekend publications such as the Sunday Times provided limited data as they reported on the events outside the focal dates. Dependence on mainstream data rather than a balance between community and national was a further limitation. The analysis pointed to media content that is classed and ideologically mediated, it also indicated that the plurality of voices encouraged by the main theoretical framework of radical democracy is highly compromised and some groups are more visible than others. As guided by the research questions the dissertation revealed various ideologies and discourses and concluded that those that were preferred by the media were mainly dominated by the elite or privileged members of society.
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; edia Content and Representation - Racialised; Gendered Classed; Voices; Listening; Media representation of protests; Print Circulation; Media closure and retrenchments; Media Trust; Radical Democracy; Symbolic annihilation and The Political economic theory of the media; SDG-4: Quality education